Unfolding Pathway of a Globular Protein by Surfactants Monitored with Raman Optical Activity - Nieto-Ortega, Belén; Hierrezuelo-Osorio, José Manuel; Carnero-Ruiz, Cristóbal; López-Navarrete, Juan Teodomiro; Casado-Cordón, Juan; Ramírez-Aguilar, Francisco Javier (ACS Publications, 2014)
Protein denaturation by surfactants has received increased attention in the last years due to its implications in topics such as pharmaceutics, cosmetics, paints, or biotechnology. This phenomenon is highly dependent on the physicochemical (structural) properties of the denaturing agents. In this work, we have measured for the first time the Raman optical activity (ROA) of bovine serum albumin (BSA) in the presence of three surfactants (anionic, cationic, and neutral), which has allowed us to detect new spectroscopic insights of the protein−surfactant interaction that conventional Raman spectroscopy cannot. Our work proposes two new groups of ROA marker bands to explore the unfolding of BSA induced by surfactants, which are related to “polar” (amide I and III modes) and “apolar” (methylene bending and phenyl breathing modes) protein sections. The appearance of the former groups is related to the initial attack of the surfactant, while the second groups relate to the hydrophobic unfolding.
Keywords: Agentes tensioactivos; ROA; Raman; BSA; surfactants